INCREASING STUDENTSâ LEARNING ACTIVITY IN MEDIA AND LEARNING RESOURCES CLASS BY USING NUMBER HEADS TOGETHER (NHT) ( A CLASSROOM ACTION RESEARCH) - Maulida, Hidya; Norliani, Norliani (English Department of Faculty of Tarbiyah and Teachers Training, 2016)
This research aims to increase studentsâ learning activity in Media and Learning Resources class. The kind of research is classroom action research conducted two cycles with the subject is the fifth semester students of English departement. Technique of collecting data is observation and analyzing quantitatively and qualitatively. Â From cycle I and cycle II,Â studentsâ learning activity is increasing . Research hypothes stated that the use ofÂ Number Heads TogetherÂ technique can increase the studentsâ learning activity can be proven. It is concluded that the use of Number Heads Together (NHT)Â can increase studentsâ learning activity in Media and Learning Resources class. The studentsâ learning activity increases 37,5% , from 25% to 62,5%. Â Number Heads Together should be developed and applied in every education level because this technique makes students are more aware that they are observed so it stimulates them to be active.